Penerapan Body Restrain Terhadap Pasien Risiko Jatuh Pasca Operasi Subarachnoid hemorrhage - Niken Briana Tasya; Ari Budiati Sri Hidayati; Muhammad Munif (An-Najat, 2024)
Hemorrhagic stroke is a type of stroke where bleeding occurs in the brain, namely intracerebral or subarachnoid space. Subarachnoid hemorrhage (SAH) is a type of hemorrhagic stroke or cerebrovascular disease that can be destructive after an intracranial aneurysm ruptures. The symptoms felt can affect physiological changes such as damage to physical mobility, so it is necessary to apply body restraints to limit movement during treatment so that patients are protected from the dangers of falls and assess MFS. Objective: to determine the effect of Body Restraint on patients at risk of falling after subarachnoid hemorrhage surgery. Method: case study with intervention using body restraints in patients at risk of falling after subarachnoid hemorrhage surgery. Carried out at the Central Surgical Installation (IBS) of PKU Muhammadiyah Hospital Yogyakarta. Results: In this study there was a positive influence on the application of Body Restraint in post-operative subarachnoid hemorrhage patients. There was a decrease in the fall risk score after the intervention was carried out for 3 consecutive days from a Morse scale score of 75 on the first day to 60 on the last day. Conclusion: applying Body Restraint to patients at risk of falling can protect patients from danger and ensure patient safety after subarachnoid hemorrhage (SAH) surgery.